Adverse event profile and associated factors following surgical voluntary medical male circumcision in two regions of Namibia, 2015-2018. - Gillian O'Bryan (Public Library of Science (PLoS), 2021)
Introduction Monitoring clinical safety of voluntary medical male circumcision (VMMC) is critical to minimize risk as VMMC programs for HIV prevention are scaled. This cross-sectional analysis describes the adverse event (AE) profile of a large-scale, routine VMMC program and identifies factors associated with the development, severity, and timing of AEs to provide recommendations for program quality improvement. Materials and methods From 2015-2018 there were 28,990 circumcisions performed in International Training and Education Center for Health (I-TECH) supported regions of Namibia in collaboration with the Ministry of Health and Social Services. Two routine follow-up visits after VMMC were scheduled to identify clients with AEs. Summary statistics were used to describe characteristics of all VMMC clients and the subset who experienced an AE. We used chi-square tests to evaluate associations between AE timing, patient age, and other patient and AE characteristics. We used a logistic regression model to explore associations between patient characteristics and AE severity. Results Of the 498 clients with AEs (AE rate of 1.7%), 40 (8%) occurred ≤2 days, 262 (53%) occurred 3-7 days, 161 (32%) between day 8 and 14, and 35 (7%) were ≥15 days post-VMMC. Early AEs (on or before day 2) tended to be severe and categorized as bleeding, while infections were the most common AEs occurring later (p<0.001). Younger clients (aged 10-14 years) experienced more infections, whereas older clients experienced more bleeding (p<0.001). Conclusions Almost 40% of AEs occurred after the second follow-up visit, of which 179 (91%) were infections. Improvements in pre-surgical and post-surgical counselling and post-operative educational materials encouraging clients to seek care at any time, adoption of alternative follow-up methods, and the addition of a third follow-up visit may improve outcomes for patients. Enhancing post-surgical counselling and emphasizing wound care for younger VMMC clients and their caregivers could help mitigate elevated risk of infection.